Sodium zirconium silicate hydrate and preparation method thereof
By using a multi-layer pushing paddle and colloidal silica with a multi-layer pushing paddle and the colloidal stabilizer without ammonia ion stabilizers during the preparation of sodium silicate water compounds, the potassium ion exchange capacity caused by ZS-7 and non-fondable substances has been successfully solved. The difficulty of cleaning in the production process realizes the preparation of high -purity products and the satisfaction of GMP production.
Patent Information
- Application Number
- CN202410447497.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-15
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-04-15
AI Technical Summary
The existing sodium zirconium silicate hydrates contain ZS-7 crystals and amorphous substances, resulting in a decrease in potassium ion exchange capacity, and the residual fine particles during the production process increases the difficulty of cleaning, which cannot meet the production requirements of drug GMP.
Use a multi-layer pushing paddle for hydrophilic crystals to avoid adding baffles on the side wall of the reactor. Through the silicon dioxide of the colloidal with an ion stabilizer without ammonia and the proper water heat crystalline conditions, it is prepared to contain ZS-7 without ZS-7 And high -purity sodium silicate aquatic compound with non -fixed substances.
The high purity preparation of sodium silicate aquatic compounds has been realized. The weight percentage content reaches more than 99 %. The potassium ion exchange rate is greater than 3.5Meq/G, which simplifies the reactor cleaning and meets the requirements of drug GMP production.
Smart Images

Figure CN118439624B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of drug synthesis, and in particular to sodium zirconosilicate hydrate and a preparation method thereof. Background Art
[0002] Hyperkalemia is a common electrolyte disorder in clinical practice. Sodium zirconium cyclosilicate is a stable "ion trap" technology. Its main component is ZS-9, an inorganic crystal. Its seven-membered ring structure is highly matched with the diameter of potassium ions. Its binding rate with potassium ions is 25 times that of other cations. It can bind to potassium ions in the digestive tract, promote the transfer of blood potassium to the intestine and excrete it from the body, thereby achieving rapid potassium reduction and long-term potassium control. Sodium zirconium cyclosilicate powder was launched in China in 2019. The original research company is ZS Pharmaceuticals, and the marketing authorization holder is AstraZeneca.
[0003] U.S. Patent No. 5,891,417 disclosed several different crystal forms of sodium zirconium silicate hydrate in 1999, namely ZS-1 to ZS-11, among which the X-ray diffraction patterns of ZS-7 and ZS-9 are as follows:
[0004]
[0005]
[0006] The 2θ angle data of ZS-7 according to the public is as follows:
[0007]
[0008] The 2θ angle data of ZS-9 according to the public is as follows:
[0009]
[0010] Where I represents the intensity of the diffraction peak, vs, s, m and w represent the relative intensity of the d-spacing. From the above data, it can be concluded that the X-ray characteristic diffraction peak 2θ angles of ZS-7 are 12.35, 14.75, 21.59, 23.63 and 29.63. The X-ray characteristic diffraction peak 2θ angles of ZS-9 are 12.12, 13.98, 15.65, 29.00 and 32.30. The X-ray diffraction peaks of the two phases are very different and have strong specificity.
[0011] The original Chinese patent CN106170283B reported the preparation method of ZS-9. The phase composition of sodium zirconium silicate hydrate prepared in Example 20 analyzed by Rietveld Method contained 16.0-25.7% ZS-7 and 14.3-22.5% amorphous crystals, and the measured potassium ion exchange capacity was only about 3.0 mEq / g. At the same time, Example 23 of the patent described the preparation of ZS-9 by adding sodium silicate to a system of sodium hydroxide and water at a 500L reactor scale through hydrothermal crystallization, with a content of 95%, and the remaining 5% being ZS-7 or amorphous substances, and the obtained product potassium ion capacity was 3.5 mEq / g, and the XRD pattern of ZS-9 with a content greater than 95% was disclosed. Therefore, the presence of ZS-7 and amorphous substances significantly reduces the potassium ion exchange capacity of the product. ZS-7 and amorphous substances do not have highly selective potassium ion exchange capacity. ZS-7 and amorphous substances can be considered as impurities of the product.
[0012] As shown in Table 1, the control strategy for the impurity limit of APIs in ICHQ3A requires that the impurity limit of APIs with a daily intake of more than 2g is 0.05%. The impurity content of sodium zirconium silicate hydrate (sodium zirconium cyclosilicate) prepared in Example 23 of Chinese patent CN106170283B is significantly higher than the impurity limit requirements specified by ICH.
[0013] Table 1 ICHQ3A Impurity Limits for New APIs
[0014]
[0015] [1] Daily intake of new API
[0016] [2] Higher reporting limits require scientific evaluation
[0017] [3] If the impurity is highly toxic, the limit value should be appropriately lowered
[0018] Therefore, preparing a sodium zirconium silicate hydrate with very low content of ZS-7 and amorphous substances or containing no ZS-7 and amorphous substances meets the control requirements of relevant impurities in medicines and has very obvious practical significance.
[0019] Patent CN108137620B discloses a reactor for producing high-purity, high potassium ion exchange capacity ZS-9 crystals, with a baffle structure on the side wall of the reactor. During the reaction, the baffle structure combined with the agitator provides significant lifting and suspension of the crystals, producing high-purity, high potassium ion exchange capacity ZS-9 crystals. However, this reactor has a major drawback. The ZS-9 product is fine particles, which will remain around the baffle during the production process, increasing the difficulty of cleaning. Cyclic production will increase the residue of the previous batch of materials, and cleaning verification cannot be confirmed during the GMP production process of pharmaceuticals. Summary of the invention
[0020] The invention provides a sodium zirconosilicate hydrate free of ZS-7 crystals and amorphous substances and a preparation method thereof. The sodium zirconosilicate hydrate has high crystalline content and excellent potassium ion exchange rate.
[0021] The technical solution of the present invention is as follows:
[0022] A sodium zirconium silicate hydrate having a molecular formula as shown in formula (I):
[0023] Na p H 2-p ZrSi 3 O 9 · X H 2 O (I)
[0024] in:
[0025] The value of "p" is 1.5<p<2;
[0026] The value of "x" is 2<x<3;
[0027] The weight percentage of the sodium zirconium silicate hydrate is at least 99%, and it does not contain ZS-7 and amorphous substances.
[0028] The X-ray diffraction patterns of ZS-7 and sodium zirconium silicate hydrate are as follows:
[0029]
[0030] The ZS-7 and amorphous impurities in sodium zirconium silicate hydrate do not have a highly selective potassium ion exchange capacity, and the ZS-7 and amorphous impurities significantly reduce the potassium ion exchange capacity of the product.
[0031] Preferably, the sodium zirconosilicate hydrate is protonated.
[0032] Preferably, the potassium ion exchange rate of the sodium zirconium silicate hydrate is greater than 3.5 mEq / g.
[0033] The sodium zirconium silicate hydrate of the present invention does not contain ZS-7 and amorphous material impurities, the weight percentage content is more than 99%, and has excellent potassium ion exchange capacity, and the potassium ion exchange rate is greater than 3.5mEq / g.
[0034] The present invention also provides a method for preparing the sodium zirconium silicate hydrate, comprising: adding colloidal silicon dioxide to an aqueous solution of sodium hydroxide, then adding zirconium acetate, subjecting the mixture slurry to hydrothermal crystallization under stirring by a stirring device, filtering, washing, protonating, and drying to obtain the sodium zirconium silicate hydrate;
[0035] The stirring device is a multi-layer propulsion stirring paddle.
[0036] The multi-layer propeller stirring blades are at least two layers of propeller stirring blades arranged on the axial direction of the stirring shaft. The propeller stirring device can make the materials circulate in the reactor, and the function is mainly volume circulation, and the up and down tumbling effect is good. The diameter of the propeller stirring device is about 1 / 4 to 1 / 3 of the inner diameter of the reactor.
[0037] In the prior art (such as patent CN108137620B), the stirring device is a layer of stirring paddles. The purity of ZS-9 in the product is improved by adding baffles around the reactor. The ZS-9 product is fine particles, which will remain around the baffles during the production process, increasing the difficulty of cleaning. Cyclic production will increase the residue of the previous batch of materials. Cleaning verification and confirmation cannot be performed during the GMP production process of pharmaceuticals. In addition, the layer of stirring paddles has strict restrictions on the size of the blades. The material is easy to sink to the bottom of the reactor, resulting in insufficient crystallization of the material, resulting in the production of amorphous substances and ZS-7 crystals.
[0038] The present invention only needs to use multi-layer propulsion stirring paddles, and does not need to add baffles on the side walls of the reactor to obtain a high-purity sodium zirconium silicate hydrate product. The reactor is easy to clean, and the quality of the raw material medicine is more guaranteed.
[0039] According to ICH rules, ZS-7 and amorphous substances are impurities in sodium zirconium silicate hydrate products. According to the limit requirements for impurities in drugs, the impurity content is very high, which poses a greater risk to preparation production. In the present invention, the inventor surprisingly found that the use of multi-layer propulsion stirring can effectively prevent the material from sinking, reduce the generation of ZS-7 and amorphous substances, and thus improve the purity and content of the sodium zirconium silicate hydrate product.
[0040] The multi-layer propulsion stirring paddle is a double-layer propulsion stirring paddle.
[0041] The reactor used in the present invention is a pressure vessel made of stainless steel or Hastelloy alloy with multi-layer propulsion stirring paddles.
[0042] Preferably, at a reaction scale of 0.5 to 1 L, the stirring speed is greater than 200 rpm and less than 350 rpm; more preferably, it is 250 to 350 rpm.
[0043] On this basis, the reactor scale can be expanded to a production scale of 100 to 5000 L, for example, 100 L, 200 L, 500 L, 1000 L, 2000 L, 5000 L.
[0044] Preferably, the colloidal silicon dioxide does not contain ammonium ions.
[0045] The colloidal silica used in the prior art is colloidal silica with an ammonium ion stabilizer. The colloidal silica with an ammonium ion stabilizer will produce ammonia gas after being subjected to high temperature and high pressure, which has a great impact on the environment. In addition, excess ammonium ions exist in the product, resulting in a decrease in the potassium ion exchange rate of the product. The inventors were surprised to find that by using colloidal silica without an ammonium ion stabilizer, the product has no ammonia smell, is more green and environmentally friendly, and the potassium ion exchange rate can reach 3.7mEq / g, and the product quality is greatly improved compared with the prior art.
[0046] Preferably, the colloidal silicon dioxide is aqueous colloidal silicon dioxide, and the content of silicon dioxide is 39.0-41.0 wt %.
[0047] Through experiments, it was found that when using aqueous colloidal silica with a content of 39.0 to 41.0 wt%, the colloidal silica has good dispersibility in water and a larger specific surface area than aqueous colloidal silica with other contents, and the sodium hydroxide reacts more thoroughly with the silica. However, when using solid silica, such as fumed silica, the reaction with sodium hydroxide is not thorough, resulting in a product with more impurities and a low potassium ion exchange rate.
[0048] Preferably, the hydrothermal crystallization temperature is 200-210°C.
[0049] Through comparative tests, it was found that when the crystallization temperature was lower than 200°C, the potassium ion exchange rate of the obtained sodium zirconium silicate hydrate was lower than 3.0 mEq / g, while when the crystallization temperature was between 200 and 210°C, the potassium ion exchange rate of the obtained sodium zirconium silicate hydrate exceeded 3.5 mEq / g.
[0050] Preferably, the hydrothermal crystallization reaction time is more than 24 hours; more preferably, it is 24 to 35 hours.
[0051] The sodium zirconium silicate hydrate is protonated sodium zirconium silicate hydrate, and its potassium exchange rate is greater than 3.5 meq / g.
[0052] Compared with the prior art, the present invention has the following beneficial effects:
[0053] (1) The sodium zirconium silicate hydrate obtained by the present invention is high-purity and does not contain ZS-7 and amorphous substances, thereby ensuring the quality control of impurities in medicines; the weight percentage content of the sodium zirconium silicate hydrate obtained is above 99%, and the potassium ion exchange capacity is greater than 3.5 meq / g;
[0054] (2) The raw materials of the present invention are simple and easy to obtain, the synthesis is green and environmentally friendly, and the potassium ion exchange rate is greatly improved;
[0055] (3) The reactor of the present invention has a simple structure and meets the GMP production requirements for pharmaceuticals. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 The XRD pattern of the product prepared in Example 1;
[0057] Figure 2 is the TGA spectrum of the product prepared in Example 1;
[0058] Figure 3 The XRD pattern of the product prepared in Example 2;
[0059] Figure 4 The XRD pattern of the product prepared in Example 4;
[0060] Figure 5 This is the XRD pattern of amorphous sodium zirconium silicate hydrate. DETAILED DESCRIPTION
[0061] The present invention will be further described in detail below in conjunction with specific examples. The method of the present invention can be implemented by many different combinations, but is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present invention more thoroughly and comprehensively understood.
[0062] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0063] Example 1
[0064] In a 1L stainless steel pressure vessel, sodium hydroxide (190 g) and water (300 mL) were mixed using a double-layer propeller stirring paddle and then cooled to room temperature. Colloidal silica Ludox without ammonium ion stabilizer was added. TM-HS-40 (200g), stirring speed is 300rpm. While maintaining the stirring speed, add zirconium acetate (160g), produce slurry after addition, add water (120mL) and maintain the stirring speed, heat the reactor to 200-210℃, maintain for 24 hours and then cool to room temperature, filter, wash the crude product with purified water (200mL) × 3, transfer the washed crude product to a glass bottle and add purified water (200mL), adjust the pH to 4.75-5.25 with hydrochloric acid, filter, and continue to wash with purified water twice, 200mL each time. After filtering, place the material in a 100℃ oven and dry under reduced pressure to constant weight, the potassium ion exchange rate is measured to be 3.7mEq / g, XRD shows that the product has no ZS-7 characteristic peak, TGA shows that there are about 2-3 crystal waters.
[0065] XRD spectra can only represent the ZS series without other crystal forms, such as ZS-7, rather than the absence of amorphous substances. Figure 5 The XRD spectrum of amorphous sodium zirconium silicate hydrate. The Rietveld Method can be used to determine whether there is amorphous material in the sample. By adding a known amount of standard sample to the mixed sample, the content of other crystalline phases with known structures in the sample can be obtained. The content of amorphous phase, i.e. amorphous sample, can be obtained from the difference between the total content of crystalline material and 1.
[0066] According to the Rietveld Method, the sodium zirconium silicate hydrate prepared by the preparation method does not contain amorphous substances, as shown in Table 2. The crystal structure model of the cubic unit cell of sodium zirconium silicate hydrate is used, such as the reference (InorChim Acta 2003, 356, 19). The model of ZS-7 is the structure of the mineral Petarasite.
[0067] Table 2
[0068] batch number Sodium Zirconium Silicate Hydrate ZS-7 Amorphous matter 231201 100% 0 0 231202 100% 0 0
[0069] KEC is potassium exchange capacity, which is calculated with reference to the formula of Example 15 of patent CN106170283B.
[0070] The sample was subjected to pattern indexing analysis of X-ray diffraction data and the results showed that it was a cubic crystal system with unit cell parameters It shows that it is a pure phase, that is, the content is close to 100%, and it does not contain ZS-7. X-ray fluorescence spectrometry (XRF) analysis determined the content of sodium, silicon, and zirconium in the sample, and determined that the silicon-zirconium ratio was 3 / 1. Solid-state nuclear magnetic resonance analysis (ssNMR) analysis showed that there were single elements such as silicon and sodium in the structure, and the surface sample was a single compound. Combined with the data of TGA crystal water, the molecular formula of the sample was derived as follows: Na1.7 H 0.3 ZrSi 3 O 9 2.7H 2 O.
[0071] Example 2
[0072] In a 1L stainless steel pressure vessel, a double-layer propeller stirring paddle was used, such as Figure 5 As shown, sodium hydroxide (190 g) and water (300 mL) were mixed and cooled to room temperature, and colloidal silica Ludox without ammonium ion stabilizer was added. TM -HS-40 (200g), stirring speed is 300rpm. At the same time, maintain the stirring speed, add zirconium acetate (160g), produce slurry after addition, add water (120mL) and maintain the stirring speed, heat the reactor to 200-210℃, maintain for 35 hours and then cool to room temperature, filter, wash the crude product with purified water (200mL) × 3, transfer the washed crude product to a glass bottle and add purified water (200mL), adjust the pH to 4.75-5.25 with hydrochloric acid, filter, and continue to wash with purified water twice, 200mL each time. After filtering, place the material in a 100℃ oven and dry under reduced pressure to constant weight. The potassium ion exchange rate is measured to be 3.7mEq / g. XRD shows that the product has no ZS-7 characteristic peak. According to the Rietveld Method analysis, the product has no amorphous substance.
[0073] After analysis, the molecular formula of the product is: Na 1.6 H 0.4 ZrSi 3 O 9 2.8H 2 O.
[0074] Comparative Example 1
[0075] In a 1L stainless steel pressure vessel, sodium hydroxide (190 g) and water (300 mL) were mixed using a single-layer propeller stirring paddle and then cooled to room temperature. Colloidal silica Ludox without ammonium ion stabilizer was added. TM-HS-40 (200g), stirring speed is 300rpm. While maintaining the stirring speed, add zirconium acetate (160g), after adding, a slurry is generated, and then add water (120mL) and maintain the stirring speed, heat the reactor to 200-210℃, maintain for 24 hours, then cool to room temperature, filter, wash the crude product with purified water (200mL) × 3, transfer the washed crude product to a glass bottle, add purified water (200mL), adjust the pH to 4.75-5.25 with hydrochloric acid, filter, and continue to wash with purified water twice, 200mL each time. After filtering, place the material in a 100℃ oven and dry under reduced pressure to constant weight. The potassium ion exchange rate is measured to be 3.3mEq / g. XRD shows that the product shows ZS-7 characteristic peaks (2θ: 14.64, 21.44, 21.98). According to the Rietveld Method analysis, the sodium zirconium silicate hydrate prepared by the preparation method contains amorphous substances, as shown in the following Table 3:
[0076] Table 3
[0077] batch number Sodium Zirconium Silicate Hydrate ZS-7 Amorphous matter 231203 93.5% 3.0% 3.5% 231204 93.2% 2.8% 4.0%
[0078] Comparative Example 2
[0079] In a 1L stainless steel pressure vessel, sodium hydroxide (190 g) and water (300 mL) were mixed using a double-layer propeller stirring paddle and then cooled to room temperature. Colloidal silica Ludox TM -AS-40 (200g), stirring speed is 300rpm. While maintaining the stirring speed, add zirconium acetate (160g), produce slurry after addition, add water (120mL) and maintain the stirring speed, heat the reactor to 200-210℃, maintain for 24 hours and then cool to room temperature, filter, the material has a strong smell of ammonia, the crude product is washed with purified water (200mL) × 3, the washed crude product is transferred to a glass bottle and purified water (200mL) is added, the pH is adjusted to 4.75-5.25 with hydrochloric acid, filtered, and continued to wash twice with purified water, 200mL each time. After filtering, the material is placed in a 100℃ oven under reduced pressure and dried to constant weight, and the potassium ion exchange rate is measured to be 3.2mEq / g.
[0080] Comparative Example 3
[0081] In a 1L stainless steel pressure vessel, sodium hydroxide (190 g) and water (300 mL) were mixed using a double-layer propeller stirring paddle and then cooled to room temperature. (80g), stirring speed is 300rpm. At the same time, maintain the stirring speed, add zirconium acetate (160g), produce slurry after addition, add water (120mL) and maintain the stirring speed, heat the reactor to 200-210℃, maintain for 24 hours and then cool to room temperature, filter, wash the crude product with purified water (200mL) × 3, transfer the washed crude product to a glass bottle and add purified water (200mL), adjust the pH to 4.75-5.25 with hydrochloric acid, filter, and continue to wash with purified water twice, 200mL each time. After filtering, place the material in a 100℃ oven and dry under reduced pressure to constant weight, and the potassium ion exchange rate is measured to be 3.1mEq / g. XRD shows that the product has more impurities.
[0082] Comparative Example 4
[0083] In a 1L stainless steel pressure vessel, sodium hydroxide (190g) and water (300mL) were mixed with a double-layer propulsion stirring paddle, cooled to room temperature, and colloidal silica (200g) without ammonium ion stabilizer was added at a stirring speed of 300rpm. While maintaining the stirring speed, zirconium acetate (160g) was added, and a slurry was produced after the addition. Water (120mL) was added and the stirring speed was maintained. The reactor was heated to 190°C, maintained for 24 hours, and then cooled to room temperature. The crude product was filtered and washed with purified water (200mL) × 3. The washed crude product was transferred to a glass bottle and purified water (200mL) was added. The pH was adjusted to 4.75-5.25 with hydrochloric acid, filtered, and washed twice with purified water, 200mL each time. After filtering, the material was placed in a 100°C oven under reduced pressure and dried to constant weight. The potassium ion exchange rate was measured to be 2.9mEq / g.
[0084] The embodiments described above provide a detailed description of the technical solutions and beneficial effects of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements and equivalent substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A sodium zirconium silicate hydrate, characterized in that: It has a molecular formula as shown in formula (I): <h2 style=";text-align:left;direction:ltr">Na<h2 style=";text-align:left;direction:ltr"> p <h2 style=";text-align:left;direction:ltr"> H<h2 style=";text-align:left;direction:ltr"> 2-p <h2 style=";text-align:left;direction:ltr"> ZrSi3O9<h2 style=";text-align:left;direction:ltr"> X <h2 style=";text-align:left;direction:ltr"> H2O(I) in: The value of "p" is 1.5<p<2; The value of "x" is 2<x<3; The weight percentage content of ZS-9 in the sodium zirconium silicate hydrate is at least 99%, and it does not contain ZS-7 and amorphous substances.
2. The sodium zirconium silicate hydrate according to claim 1, characterized in that The X-ray diffraction pattern of ZS-7 is as follows:
3. The sodium zirconium silicate hydrate according to claim 1, characterized in that The X-ray diffraction pattern of ZS-9 is as follows:
4. The sodium zirconium silicate hydrate according to claim 1, characterized in that The potassium ion exchange rate of the sodium zirconium silicate hydrate is greater than 3.5 mEq / g.
5. A method for preparing sodium zirconium silicate hydrate according to any one of claims 1 to 4, characterized in that: include: The colloidal silicon dioxide is added to an aqueous solution of sodium hydroxide, and then zirconium acetate is added, and the mixture slurry is subjected to hydrothermal crystallization under stirring by a stirring device, and then filtered, washed, protonated, and dried to obtain the product; the stirring device is a multi-layer propulsion stirring paddle; The colloidal silicon dioxide does not contain ammonium ions; the colloidal silicon dioxide is aqueous colloidal silicon dioxide, and the content of silicon dioxide is 39.0-41.0wt%; The hydrothermal crystallization temperature is 200-210°C; the hydrothermal crystallization time is more than 24 hours.
Citation Information
Patent Citations
Microporous zirconium silicate for the treatment of hyperkalemia
CN106170283B
Expanding the use of zirconium silicate compositions and their application methods
CN108137620B
Zirconium silicate and zirconium germanate molecular sieves and process using the same
US5891417A
Microporous zirconium silicate for the treatment of hyperkalemia
CN103534209A
Microporous zirconium silicate for treating hyperkalemia
CN104797263A